The Impact of AI Personalization on User Satisfaction and Usage Intention in B2B Agricultural E-Platforms - Sularto, Lana; Hermawati, Sri; Sugiarti, Rina; A. R., Dewi; Lestari, Ira Phajar; Sugeru, Herik (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of agribusiness e-commerce platforms has highlighted the importance of user satisfaction and continued use for their success. This study aimed to evaluate user satisfaction and usage intention, focusing on key factors influencing user behavior. A quantitative approach was employed, collecting data from 200 respondents using a 5-point Likert scale questionnaire. The analysis used multiple linear regression to assess the impact of content, accuracy, format, ease of use, and timeliness on satisfaction, and partial least squares structural equation modeling to examine relationships involving artificial intelligence personalization, content quality, system quality, usability, satisfaction, and usage intention. The findings showed that content, accuracy, and timeliness strongly drive satisfaction, while ease of use and format revealed interface challenges. Artificial intelligence personalization, content quality, and system quality significantly influenced satisfaction and usage intention, but usability had no direct effect on usage intention. satisfaction mediated the effects of artificial intelligence personalization and system quality on usage intention. This study concludes that improving interface design and enhancing personalized, reliable systems can boost user satisfaction and retention, offering valuable insights for agribusiness e-commerce platforms to optimize user experience and support sustainable growth.